Utilizing Preservice English Teachers Strategies and Classroom Management at Junior High School in Rejang Lebong Regency - Apriani, Eka (ENGLISH FRANCA : Academic Journal of English Language and Education, 2017)
ABSTRACT The objective of this research is aimed to know what are the most strategies and classroom management which are used by Preservice English Teacher at STAIN Curup in the academic year 2016/2017. The total of English Teacher was 7 teachers which as cooperating teacher of 17 preservice English Teacher. The types of english teaching strategies used by preservive English teacher were: (1) Task-Based Language Learning (100%) and (2) Cooperative Learning (100%); (3) Grapic Organizers (29%); (4) Technology (5.8%); (5) Roleplay (5.8%); (6) Storytelling (11.7%); (7) Vocabulary Building (11.7%); (8) Summarizing and Notetaking (5.8%); and (9) Analysis of Student Work (5.8%). The most strategies used by preservice english teacher (>50%) were Task-Based Language Learning and Cooperative Learning (100%). The types of classroom management used by preservive English teacher were: (1) Maintaning Discipline (58.5%), (2) giving feedback (100%), and classroom interaction (17.6%). The most classroom management used by preservice english teacher (>50%) were giving feedback and maintaning discipline. Keywords: Classroom Management, Presrvice English Teacher, Teaching Strategies